PENGARUH FINANCIAL DISTRESS, BESARAN MODAL, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI - Shieren Novelinda; Ninik Anggraini; Eni Srihastuti (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of financial distress, capital size, and leverage on accounting conservatism in transportation sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. This research uses a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from annual financial reports. The sample consists of 10 transportation companies selected using purposive sampling. The results show that financial distress has a significant negative effect on accounting conservatism, capital size has a significant positive effect, while leverage has no significant effect. Simultaneously, these variables have a significant effect on accounting conservatism with a contribution of 26.9%.